2016
DOI: 10.5099/aj160300208
|View full text |Cite
|
Sign up to set email alerts
|

Nox2ds-Tat, A Peptide Inhibitor of NADPH Oxidase, Exerts Cardioprotective Effects by Attenuating Reactive Oxygen Species During Ischemia/Reperfusion Injury

Abstract: Myocardial infarction is a form of ischemia/reperfusion (I/R) injury that causes cardiac contractile dysfunction and cell death. I/R injury is mediated, in part, by decreased endothelial-derived nitric oxide (NO) bioavailability and increased reactive oxygen species (ROS) resulting in cell death. Cytokines released from I/R tissue activate G-protein coupled receptors that in turn stimulate NADPH oxidase to produce ROS. Thus, administration of a NADPH oxidase peptide inhibitor, Nox2ds-tat (formerly known as gp9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…At the end of the experiment, the heart was crosssectioned into 2 mm sections from apex to base. The heart crosssections were subjected to 1% Triphenyltetrazolium Chloride (TTC) staining for 15 min at 37 °C to determine infarct size as previously described [20,27,28].…”
Section: Myocardial I/r Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…At the end of the experiment, the heart was crosssectioned into 2 mm sections from apex to base. The heart crosssections were subjected to 1% Triphenyltetrazolium Chloride (TTC) staining for 15 min at 37 °C to determine infarct size as previously described [20,27,28].…”
Section: Myocardial I/r Proceduresmentioning
confidence: 99%
“…The microsensors were connected to a free radical analyzer (Apollo 4000, WPI, Inc., Sarasota, FL). This arrangement allowed for real-time measurements of H 2 O 2 or NO release as previously described [18,20,29]. One limb was subjected to I/R via clamping of the femoral artery and vein for 30 min followed by reperfusion for 45 min.…”
Section: Hindlimb I/r Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, good results have been obtained in the evaluation of Nox2ds-tat, which includes a portion of the chemical structure from compounds of the first generation (the tat portion), which was included to improve Nox2ds delivery into the cell. Several articles have reported that the inhibitory activity of gp91ds-tat is better in a cell-free system in comparison to cell system evaluation [ 144 ]. In addition, very limited oral bioavailability has been reported in several articles [ 145 , 146 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that both UC and CD are caused by inflammation-related cytokine-driven mixed infiltrates in the intestinal mucosa [7] . Some proinflammatory cytokines such as TNF-α, IL-1b, IL-6, and IL-17 also play crucial roles in disease pathogenesis [8][9][10]. Inhibition of lipid peroxidation or scavenging of oxygen free radicals would a rationale for therapeutic modulation with antioxidants [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%